Wayang Klitik: Form and Function in the Bersih Sendang Ceremony in Wonosoco Village - Iskandar, Wahyu; Ibnan Syarif, Muhammad; Wadiyo, Wadiyo (Catharsis, 2020)
Wayang klitik is one of the traditional performances that are sacred as a means of bersih sendang ceremonial which is still sustainable today in Wonosoco Village, Undaan District, Kudus Regency. The purpose of this research is to examine the form of puppets and their functions in the bersih sendang ceremony. This study uses qualitative methods with interview data collection techniques, observation and document study. The data validity technique is based on credibility criteria, using data triangulation . Analysis of data is done through data collection, data reduction , data presentation, and data verification. The results of the study, regarding the shape of the wayang klitik made of flat wood formed according to the puppet character, carved and colored with simple decorative techniques, the puppet groups can be distinguished from face color , face shape , accessories, and body position. Wayang klitik in the bersih sendang ceremony has three functions, they are a personal function, a social function and a practical physical function. Personal function as a form of expression wayang klitik maker from realize his idea, social function as a means of rituals in the bersih sendang ceremony, entertainment exciting, educational media to the public, means of communication to God and dhanyang village, and physical function wayang klitik as props/puppets that portray the characters in the story that are playing.